Investigating the Degradability of HDPE, LDPE, PE-BIO, and PE-OXO Films under UV-B Radiation - Martínez-Romo, A.; González-Mota, R.; Soto-Bernal, J. J.; Rosales-Candelas, I. (Journal of Spectroscopy, 2015)
The changes in structural properties of high density polyethylene films (HDPE), low density polyethylene films (LDPE), biodegradable polyethylene (PE-BIO), and oxodegradable polyethylene (PE-OXO) films exposed to UV-B radiation were studied. The carbonyl (ICO) and vinyl (IV) index, the crystalline phase fraction, and the dichroic ratio were used to evaluate the photooxidation of these polymers. The results obtained show that LDPE and HDPE undergo a major degree of oxidation and an increase in the crystalline phase fraction comparing to PE-BIO and PE-OXO. If the LDPE and HDPE are pretreated by an accurate radiation UV-B dosage before its different commercial uses or in its final disposition, they can become an option for biodegradable material without the necessity of adding organic agents or photosensitizers.